Applications of inorganic nanoparticles in the diagnosis and therapy of atherosclerosis. (29th May 2020) - Dai, Ting; He, Wenming; Yao, Chenyang; Ma, Xuehua; Ren, Wenzhi; Mai, Yifeng; Wu, Aiguo
Abstract : This review focuses on recent advances in inorganic nanoparticles based dual-model imaging and therapeutic approaches for anti-atherosclerosis, including clinical trials. Abstract : Atherosclerosis is a chronic progressive disease, which may result in serious clinical outcomes, such as acute heart events or stroke with high mortality. At present, the clinical problems of atherosclerosis mainly consist of the difficulty in confirming the plaques or identifying the stability of the plaques in the early phase and the shortage of valid treatments. Fortunately, with the development of nanotechnology, various inorganic nanoparticles with imaging enhancement and noninvasive therapy functions have been studied in the imaging and treatment of atherosclerosis, which has brought new hope to patients. This review focuses on the recent progress in the use of inorganic nanoparticles in the diagnosis and therapy of atherosclerosis, including the key processes in the development of atherosclerosis and the mainly involved cells, inorganic nanoparticle-based dual-mode imaging methods classified by the types of targeting cells, and inorganic nanoparticle-based therapeutic approaches, such as photothermal therapy (PTT), photodynamic therapy (PDT), sonodynamic therapy (SDT), drug delivery, gene therapy and imaging-guided therapy for atherosclerosis. Finally, this review discusses the challenges and directions of inorganic nanoparticles in potential clinical translation of anti-atherosclerosis in future. We believe this review will enable readers to systematically understand the progress of the inorganic nanoparticle-based imaging and therapy of atherosclerosis and therefore promote the further development of anti-atherosclerosis.